Design and optimization of bilayered tablet of Hydrochlorothiazide using the Quality-by-Design approach - Dholariya, Yatin N; Bansod, Yogesh B; Vora, Rahul M; Mittal, Sandeep S; Shirsat, Ajinath Eknath; Bhingare, Chandrashekhar L (International Journal of Pharmaceutical Investigation)
Aim: The aim of the present study is to develop an optimize bilayered tablet using Hydrochlorothiazide (HCTZ) as a model drug candidate using quality by design (QbD) approach. Introduction and Method: The bilayered tablet gives biphasic drug release through loading dose; prepared using croscarmellose sodium a superdisintegrant and maintenance dose using several viscosity grades of hydrophilic polymers. The fundamental principle of QbD is to demonstrate understanding and control of pharmaceutical processes so as to deliver high quality pharmaceutical products with wide opportunities for continuous improvement. Risk assessment was carried out and subsequently 22 factorial designs in duplicate was selected to carry out design of experimentation (DOE) for evaluating the interactions and effects of the design factors on critical quality attribute. The design space was obtained by applying DOE and multivariate analysis, so as to ensure desired disintegration time (DT) and drug release is achieved. Bilayered tablet were evaluated for hardness, thickness, friability, drug content uniformity and in vitro drug dissolution. Result: Optimized formulation obtained from the design space exhibits DT of around 70 s, while DR T95% (time required to release 95% of the drug) was about 720 min. Kinetic studies of formulations revealed that erosion is the predominant mechanism for drug release. Conclusion: From the obtained results; it was concluded that independent variables have a signifi cant effect over the dependent responses, which can be deduced from half normal plots, pareto charts and surface response graphs. The predicted values matched well with the experimental values and the result demonstrates the feasibility of the design model in the development and optimization of HCTZ bilayered tablet.
Keywords: Bilayered tablets; Design of experiment; Design space; Quality-by-design; Surface response plot